Comparative leaf anatomy of selected medicinal plants in Acanthaceae - Che Amri, Che Nurul Aini; Tajudin, Nur Shuhada; Shahari, Rozilawati; Azmi, Fatin Munirah; Talip, Noraini; Mohamad, Abdul Latiff (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Comparative leaf anatomy study were conducted in three taxa of Acanthaceae from peninsular Malaysia. Three chosen taxa were Acanthus ebracreatus (Vahl), Andrographis paniculata (Burm.f.) Wall. ex Nees and Chroesthes longifolia (Wight) B. Hansen which is commonly used as traditional medicine especially in peninsular Malaysia. The main objective is to identify the leaf anatomical characteristics that can be used in plant identification and also for supportive data in plant classification. The procedures involved such as cross section using sliding microtome on the petiole, lamina, midribs and marginal, leaf clearing and observation under light microscope. Results have shown the similarities and variations in leaf anatomical characteristics. The anatomical characteristics observed include petiole and midrib outlines, patterns of petiole and midrib vascular bundles, presence of cystolith cells, presence of hypodermis layers in lamina and presence and types of trichomes. In conclusion, results showed that anatomical characteristics have taxonomic significance that can be used in classification especially at species level.